The effect of skin temperature on performance during a 7.5-km cycling time trial - Levels, K.; de Koning, J. J.; Foster, C.; Daanen, H. A. M. (European Journal of Applied Physiology, 2012)
Aerobic exercise performance is seriously compromised in the heat. Possibly, a high skin temperature causes a rating of perceived exertion (RPE)-mediated decrease in exercise intensity. The purpose of this study was to determine the effect of skin temperature on power output during a 7.5-km cycling time trial. Thirteen well-trained male subjects performed a 7.5-km cycling time trial at 15°C and 50% relative humidity (CONTROL), with radiative heat stress during the time trial, and with (PRECOOL) or without (HEAT) precooling. Heat stress was applied by infrared heaters positioned in front of the cycle ergometer between 1.5 and 6.0 km. Skin, rectal, and pill temperature, power output, heart rate, and RPE were measured during the trial. Despite the lower mean skin temperature at the start of the time trial for PRECOOL compared to HEAT (-2.1 ± 0.7°C; P < 0.01) and CONTROL (-1.8 ± 0.6°C; P < 0.05), and a greater increase in mean skin temperature during the heat stress period for PRECOOL (4.5 ± 1.0°C) and HEAT (3.9 ± 0.8°C) than for CONTROL (-0.3 ± 0.6°C; P < 0.01), no differences in power output were found between HEAT (273 ± 45 W) and CONTROL (284 ± 43 W; P = 0.11) and between HEAT and PRECOOL (266 ± 50 W; P = 0.47). Power output during the time trial was greater for CONTROL than for PRECOOL (P < 0.05). Additionally, no differences were observed in core temperature measures, HR, and RPE. Skin temperature does not affect the selection and modulation of exercise intensity in a 7.5-km cycling time trial.